2014
DOI: 10.1182/blood-2013-09-529537
|View full text |Cite|
|
Sign up to set email alerts
|

Preclinical targeting of human acute myeloid leukemia and myeloablation using chimeric antigen receptor–modified T cells

Abstract: Key Points• Targeting of CD123 via CAR-engineered T cells results in rejection of human AML and myeloablation in mouse models.Many patients with acute myeloid leukemia (AML) are incurable with chemotherapy and may benefit from novel approaches. One such approach involves the transfer of T cells engineered to express chimeric antigen receptors (CARs) for a specific cell-surface antigen. This strategy depends upon preferential expression of the target on tumor cells. To date, the lack of AML-specific surface mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
404
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(420 citation statements)
references
References 45 publications
10
404
2
4
Order By: Relevance
“…Thus among the strategies under development, DARTs may have superior qualities over BiTEs. When compared with chimeric T cell constructs (CARs) DARTs have the advantage that the requirement for in vitro T cell gene transduction is avoided (13,14). To optimize the physical properties of the chimeric antibody for AML treatment the antibody design ensures that the CD123/DART is more avid for the leukemic cell than the T cell, ensuring that T cells are preferentially bound by antibodies that have reached their target.…”
Section: Antibody Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus among the strategies under development, DARTs may have superior qualities over BiTEs. When compared with chimeric T cell constructs (CARs) DARTs have the advantage that the requirement for in vitro T cell gene transduction is avoided (13,14). To optimize the physical properties of the chimeric antibody for AML treatment the antibody design ensures that the CD123/DART is more avid for the leukemic cell than the T cell, ensuring that T cells are preferentially bound by antibodies that have reached their target.…”
Section: Antibody Designmentioning
confidence: 99%
“…Recombinant technology is used to link the variable heavy and light domains of two antibodies as a single 55 kDa polypeptide chain. In clinical (12); (II) chimeric antigen receptor T cell using anti CD123 to target myeloid cells (13,14) (not yet in clinical trial); (III) single polypeptide chain bispecific engager antibodies (BiTE) recognizing CD3 and CD3 (15) or CD123 (16); (IV) double polypeptide chain dual affinity retargeting antibodies (DART) recognizing CD3 and CD123 (17,18). AML, acute myelogenous leukemia; VL, light chain; VH, heavy chain; CD3z, zeta chain of CD3; Co-stim, costimulatory molecules.…”
Section: Antibody Designmentioning
confidence: 99%
“…(Gill et al 2014, Mardiros et al 2013) Mardiros et al (2013) reported potent efficacy of two CD123-targeted CARs generated using a lentiviral vector and targeting two distinct scFvs binding two discrete epitopes. These CD123-directed CAR T-cells could be generated from both healthy donors and patients, contained both CD8+ and CD4+ T-cells, and effectively killed CD123+ AML cell lines and autologous blasts.…”
Section: Chimeric Antigen Receptor-modified T-cellsmentioning
confidence: 99%
“…While persistence of CD123 CAR T cells (correlating with long-term animal survival) was only observed in the Penn study utilizing the 41BB-CD3ζ construct, significant on-target off–tumour toxicity of myeloid cells, B cells and platelets occurred. (Gill et al 2014) These results have led to recently opened clinical trials, which will not only evaluate safety and efficacy of these constructs, but also will provide insight into the long-term effects of CD123-CAR T-cells on haematopoiesis (NCT02159495; NCT02623582).…”
Section: Chimeric Antigen Receptor-modified T-cellsmentioning
confidence: 99%
“…Additionally, CD123-CAR-T cells exhibited anti-leukemic activity in vivo in a xenogeneic AML model. Gill and colleagues suggested that CAR-T123-based myeloablation might be used as a novel conditioning regimen for hematopoietic cell transplantations (Gill et al, 2014).…”
Section: Published Clinical Outcomes Of Adoptive Therapy With Car-modmentioning
confidence: 99%